Selection of FCSRJ Best Papers, the Outstanding Paper, and the Emerging Scholar. (31st December 2019) - DeVaney, Sharon A.
Abstract : Winners of the Best Papers published in FCSRJ during the previous year are honored at the annual conference of the American Association of Family and Consumer Sciences (AAFCS). Criteria for the Best Paper Award include originality of the topic, strength of the research methodology, and potential contribution to family and consumer sciences. There is a separate award that focuses on tenure‐track Assistant Professors; it is titled the Emerging Scholar Award. The presentation of awards for the Best Papers was established in 2009 by the previous Editor of the journal, and it has been continued each year.